A novel MR-conditional cam-based automatic prostate biopsy device. (May 2023) - Liu, Rongrong; Anique, Farrukh; Chen, Rongwan; Oh, Sung Suk; Jo, Jung Ki; Ko, Seong Young
Abstract: Biopsy is the most commonly used method for diagnosing prostate cancer, in which a biopsy gun is used to obtain the tissue samples. The outstanding performance of magnetic resonance imaging (MRI) for soft tissue can provide better medical guidance for prostate biopsy. This paper reports an automatic biopsy device that can be used in the MRI environment and that is expected to be used together with the MR conditional robotic prostate biopsy system. This paper proposes a compact cam-based automatic biopsy device that can perform all actions required for prostate biopsy sampling procedure using a single actuator. Its design concept, implementation, required force analysis, sampling performance evaluation, and MR compatibility evaluation are also provided. The experimental evaluation showed that the tissue sampling process can be easily and completely performed using the proposed automatic biopsy device, and that its sampling performance is comparable to that of the existing commercially available manual biopsy gun. MR compatibility test showed that an 18.7% reduction in the signal-to-noise ratio when the device was operating.